Green Tea Catechins, (−)‐Catechin Gallate, and (−)‐Gallocatechin Gallate are Potent Inhibitors of ABA‐Induced Stomatal Closure. Issue 21 (7th May 2022) - Sato, Kanane; Saito, Shunya; Endo, Kohsuke; Kono, Masaru; Kakei, Taishin; Taketa, Haruka; Kato, Megumi; Hamamoto, Shin; Grenzi, Matteo; Costa, Alex; Munemasa, Shintaro; Murata, Yoshiyuki; et al.
Abstract: Stomatal movement is indispensable for plant growth and survival in response to environmental stimuli. Cytosolic Ca 2+ elevation plays a crucial role in ABA‐induced stomatal closure during drought stress; however, to what extent the Ca 2+ movement across the plasma membrane from the apoplast to the cytosol contributes to this process still needs clarification. Here the authors identify (−)‐catechin gallate (CG) and (−)‐gallocatechin gallate (GCG), components of green tea, as inhibitors of voltage‐dependent K + channels which regulate K + fluxes in Arabidopsis thaliana guard cells. In Arabidopsis guard cells CG/GCG prevent ABA‐induced: i) membrane depolarization; ii) activation of Ca 2+ permeable cation ( I Ca ) channels; and iii) cytosolic Ca 2+ transients. In whole Arabidopsis plants co‐treatment with CG/GCG and ABA suppressed ABA‐induced stomatal closure and surface temperature increase. Similar to ABA, CG/GCG inhibited stomatal closure is elicited by the elicitor peptide, flg22 but has no impact on dark‐induced stomatal closure or light‐ and fusicoccin‐induced stomatal opening, suggesting that the inhibitory effect of CG/GCG is associated with Ca 2+ ‐related signaling pathways. This study further supports the crucial role of I Ca channels of the plasma membrane in ABA‐induced stomatal closure. Moreover, CG and GCG represent a new tool for the study of abiotic or biotic stress‐induced signal transduction pathways. Abstract : Ingredients of green tea affect the growth of Arabidopsis thaliana under drought conditions. Catechin gallates and gallocatechin gallates inhibit plasma membrane‐located K + channels and prevent Ca 2+ entry in Arabidopsis guard cells. These catechin derivates are potent natural chemical regulators controlling plant growth and enabling the study of drought‐induced signaling pathways in guard cells.